An Analysis Tool for Cryptographic Designs Based on Chaotic Systems - Aydın, Yılmaz; Özkaynak, Fatih (My University, 2023)
Chaos-based cryptography research is one of the application areas for chaotic systems. Numerous design studies have been put up that take use of the connection between chaos and cryptography. This study has demonstrated how to exploit this relationship to decrypt cryptography designs. It has been looked at if chaos analysis techniques may be used to analyze cryptography protocols. The effectiveness of random number generators has been evaluated using Lyapunov exponents, a chaos analysis technique. The findings of the investigation demonstrated that Lyapunov exponents can be utilized as a standard in assessing random number generators. The paper highlights the issues with the NIST test suite, a popular method of analysis for assessing the statistical characteristics of random number generators. These issues have been seen to not exist with the new test tool that has been suggested. These findings demonstrate that the suggested strategy can be successfully applied in a variety of future applications.
Keywords: Chaos; Cryptography; Lyapunov Exponents; Random Numbers